Associations between the supply and utilization of primary care and newborn, children and maternal health in rural counties of Guangdong Province, China. (19th March 2020) - Ke, Naiqi; Ma, Yuanzhu; Luo, Zhuojun; Xu, Shuyi; Kuang, Li
Abstract: Background: The Chinese government is ambitious regarding strengthening the primary care system for women and children. Primary care contributes to better health outcomes among neonates, infants, children and pregnant women, especially for vulnerable groups. However, few published studies have examined this issue in China. Objective: This study examined whether greater supply and utilization of primary care was associated with improved health outcomes among targeted populations in the total and interprovincial migrant populations in the rural counties of Guangdong Province, China. Methods: This ecological study analysed annual panel data from all 63 rural counties in Guangdong Province from 2014 to 2016 ( n = 189). A linear random-effects panel data model was applied. Results: Higher proportions of primary care visits were significantly associated with reduced incidences of low birth weight ( P < 0.05) and preterm birth rates ( P < 0.05) for the total population, and were significantly associated with reduced infant ( P < 0.1) and under-five ( P < 0.01) mortality rates for migrants. Greater primary care physician supply was significantly associated with reduced maternal mortality ( P < 0.1) rates among migrants. However, primary care indicators were insignificant for both the total and migrant populations regarding neonatal mortality rates, as well as the infant and under-five mortality rates in the total population ( P > 0.1). Conclusions: These findings support existing evidence regarding associations between primary care and improved health outcomes among newborns, children and pregnant women, especially for disadvantaged populations. However, associations were not significant for all studied health outcomes, implying the need for further study.